Synthesis, Structural Characterization And Antimicrobial Activities Of Some Transition Metal Complexes Containing 2- Acetonaphthone - A.P. MISHRA,; D.K. MISHRA, (International Journal of Pharma and Bio Sciences, 2011)
New some Schiff bases and their Co(II), Ni(II) and Cu(II) complexes formed by the condensation of 2-acetonaphthone with 2-Amino-4-chlorophenol (AACP), 2-amino-4-methylbenzothiazole (AABT) and 2-aminothiazole (ACAT). These compounds have been characterized by elemental analysis, FT-IR, FAB-mass, molar conductance, electronic spectra, ESR and magnetic susceptibility. FAB-mass data show degradation pattern of the complexes. All the complexes are colored and stable towards air and moisture. The complexes exhibit coordination number to be 4 and 6. The Schiff base and metal complexes show a good activity against the bacteria; Staphylococcus aureus, Escherichia coli and B. subtilis and fungi Aspergillus niger and Candida albicans. The antimicrobial results also indicate that the metal complexes are better antimicrobial agents as compared to the Schiff bases.